Immigrant Rights in the Shadows of Citizenship - Buff, Rachel Ida (Nation of Nations, 2008)
Punctuated by marches across the United States in the spring of 2006, immigrant rights has reemerged as a significant and highly visible political issue. Immigrant Rights in the Shadows of U.S. Citizenship brings prominent activists and scholars together to examine the emergence and significance of the contemporary immigrant rights movement. Contributors place the contemporary immigrant rights movement in historical and comparative contexts by looking at the ways immigrants and their allies have staked claims to rights in the past, and by examining movements based in different communities around the United States. Scholars explain the evolution of immigration policy, and analyze current conflicts around issues of immigrant rights; activists engaged in the current movement document the ways in which coalitions have been built among immigrants from different nations, and between immigrant and native born peoples. The essays examine the ways in which questions of immigrant rights engage broader issues of identity, including gender, race, and sexuality